Analytical adjoint discrete ordinates formulation for monoenergetic slab-geometry source-detector calculations - Pazinatto, C. B.; Barros, R.C.; Barichello, L.B. (International Journal of Nuclear Energy Science and Technology, 2016)
n/a
n/a